Reference values and improvement of aerodynamic drag in professional cyclists - Garcia-Lopez, J.; Rodriguez-Marroyo, J. A.; Juneau, C.-E.; Peleteiro, J.; Cordova Martinez, A.; Villa, J. G. (Journal of Sports Sciences, 2008)
The aims of this study were to measure the aerodynamic drag in professional cyclists, to obtain aerodynamic drag reference values in static and effort positions, to improve the cyclists' aerodynamic drag by modifying their position and cycle equipment, and to evaluate the advantages and disadvantages of these modifications. The study was performed in a wind tunnel with five professional cyclists. Four positions were assessed with a time-trial bike and one position with a standard racing bike. In all positions, aerodynamic drag and kinematic variables were recorded. The drag area for the time-trial bike was 31% higher in the effort than static position, and lower than for the standard racing bike. Changes in the cyclists' position decreased the aerodynamic drag by 14%. The aero-helmet was not favourable for all cyclists. The reliability of aerodynamic drag measures in the wind tunnel was high (r > 0.96, coefficient of variation < 2%). In conclusion, we measured and improved the aerodynamic drag in professional cyclists. Our results were better than those of other researchers who did not assess aerodynamic drag during effort at race pace and who employed different wheels. The efficiency of the aero-helmet, and the validity, reliability, and sensitivity of the wind tunnel and aerodynamic field testing were addressed.